2016
DOI: 10.1007/s00436-016-5100-8
|View full text |Cite
|
Sign up to set email alerts
|

The importance of wild fish in the epidemiology of Clonorchis sinensis in Vietnam

Abstract: Preliminary findings of a high prevalence of Clonorchis sinensis in wild-caught fish in a North Vietnam reservoir (Thac Ba reservoir, Yen Bai Province) prompted a longitudinal epidemiological study of fish infections. Monthly collections of fish from September 2014 to August 2015 were processed for recovery of metacercariae; 1219 fish, representing 22 species, were examined. Seven species were infected with C. sinensis metacercariae. Four species, Toxabramis houdemeri, Hemiculter leucisculus, Cultrichthys eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…In this study, the fish species reported as being used to prepare raw fish dishes are known to be infection sources of C . sinensis in Vietnam [ 24 , 32 35 ]. A significant association was observed between the source of raw fish dishes and province.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the fish species reported as being used to prepare raw fish dishes are known to be infection sources of C . sinensis in Vietnam [ 24 , 32 35 ]. A significant association was observed between the source of raw fish dishes and province.…”
Section: Discussionmentioning
confidence: 99%
“…We selected these two provinces because recent studies suggested a high endemicity of clonorchiasis: a prevalence of 17% was reported in a commune in Thanh Hoa [18], a coastal province, and more than 36% in a mountainous area of Yen Bai province [23]. Moreover, in these two provinces, raw fish consumption is common [18,24].…”
Section: Study Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggest that temperature is the most important regulating factor in China (Li, Yang, & Wang, 2014; Xu et al., 2005). Additionally, there is a significant difference in C. sinensis infection in fish between the dry‐cool and rainy‐warm seasons at the Thac Ba Reservoir in Vietnam (Bui et al., 2016). In summer and autumn, the temperature and humidity are beneficial to C. sinensis transmission between intermediate hosts (Li et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Pungtungia herzi and Zacco platypus have a higher infection rate of C. sinensis metacercariae and are popularly eaten raw in Korea. Approximately 45 species of freshwater fish are known to carry C. sinensis metacercariae in Vietnam (Bui et al., 2016; De, Le, & Murrell, 2012; Hung et al., 2015; Kino, Inaba, De, Chau, & Sano, 1998; Phan, Bui, Nguyen, & Murrell, 2016; Phan, Ersboll, et al, 2010; Phan, Ersbøll, et al, 2010). These species include Hypophthalmichthys molitrix , Ct. idella , Labeo rohita and Cirrhinus mrigala , all eaten raw by local people.…”
Section: Discussionmentioning
confidence: 99%